Plasmapheresis in acute disseminated encephalomyelitis associated with anti-MOG antibodies – Two clinical cases - Soares, Joana (2022)
Acute disseminated encephalomyelitis (ADEM) is an acute demyelinating disorder of the central nervous system. ADEM should be suspected when a patient develops multifocal neurologic abnormalities with encephalopathy, especially if occurring after a viral infection or immunization. In this study, the authors describe two cases of ADEM with positive anti-myelin oligodendrocyte glycoprotein (MOG) antibodies requiring hospitalization in a Pediatric Intensive Care Unit and plasmapheresis treatment.